Library Anxiety Among the Students of the Deparment of Information and Records Management, Kastamonu University - Demi̇r, Güler; Güneş, Ayşenur; Çakmakkaya, İlker (Kastamonu Egitim Dergisi, 2018)
It is already known that library anxiety is a common issue which causes many negative effects on students’ success and can even lead to library use avoidance. The main aim of this study is to examine if the undergraduate students of Information and Records Management in Kastamonu University have experienced library anxiety and to determine the level of experienced anxiety. It is also examined whether library anxiety they feel, was related to trait anxiety of those undergraduate students. The department of Information and Records Management in the Faculty of Science and Letters, in Kastamonu University was established in 2006 and began to admit students in 2014, and the current student population of the department (2015) has risen to 78. First, it was measured if there is a relationship between two variables; trait and state anxiety of 57 undergraduate students by Zung Self Rating Scale for depression. Then library anxiety was measured using the Bostick’s Library Anxiety Scale. The survey’s findings showed that about 77 percent of the students experienced library anxiety. Besides it was also found that the students’ library anxiety is independent from their trait anxiety which its level is 40,8.
Keywords: Eğitim Üzerine Çalışmalar; Studies on Education; üniversite öğrencileri; bilgi ve belge yönetimi; sürekli kaygı; durumluluk kaygı; kütüphane kaygısı; university students; information and records management; trait anxiety; state anxiety; library anxiety; 4. Education